Dose-Dependent Internalization and Externalization Integrity Study of Newly Synthesized 99mTc-Thymoquinone Radiopharmaceutical as Cancer Theranostic Agent. Issue 2 (22nd April 2020) - Tariq, Saima; Naqvi, Syed Ali Raza; Naz, Sumaira; Mubarik, Muhammad Samee; Yaseen, Muhammad; Riaz, Muhammad; Shah, Syed Muhammad Ali; Rafi, Muhammad; Roohi, Samina
Thymoquinone (TQ) is a bioactive phytochemical isolated from Nigella sativa and has been investigated for biochemical and biological activities in both in vitro and in vivo models. It is best known for its anticancer activities. Thymoquinone accomplishes anticancer activities through targeting multiple cancer markers including PPAR-γ, PTEN, P53, P73, STAT3, and generation of reactive oxygen species at the cancer cell surface. The radiolabeling of TQ with γ- and β-emitter radionuclide could be used as cancer diagnostic or therapeutic radiopharmaceutical, respectively. In this study, we are reporting the radiolabeling of TQ with technetium-99m ( 99m Tc), stability in saline and blood serum, internalization and externalization of 99m Tc-TQ using rhabdomyosarcoma cancer cells line. The quality control study revealed more than 95% labeling yield and stable in blood serum up to 4 hours. In vitro internalization rate was recorded 27.08% ± 0.95% at 1 hour post 2 hours internalization period and comparatively slow externalization. The results of this study are quite encourging and could be investigated for further key preclinical parameters to enter phase I clinical trials.